2020
DOI: 10.3390/cells9102217
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory Treatment of Canavanine and Arginine Deprivation Efficiently Targets Human Glioblastoma Cells via Pleiotropic Mechanisms

Abstract: Glioblastomas are the most frequent and aggressive form of primary brain tumors with no efficient cure. However, they often exhibit specific metabolic shifts that include deficiency in the biosynthesis of and dependence on certain exogenous amino acids. Here, we evaluated, in vitro, a novel combinatory antiglioblastoma approach based on arginine deprivation and canavanine, an arginine analogue of plant origin, using two human glioblastoma cell models, U251MG and U87MG. The combinatory treatment profoundly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…It was shown, among others, that polyphenolic compounds apart from the mentioned mutual combinations could also be combined with other natural compounds such as sugar derivatives, glycosides, peptides, and amino acids [ 51 ]. These studies seemed to be highly relevant in the context of our recent report showing that plant-derived amino acid canavanine (an arginine analog) had a strong cytotoxic effect on two human glioblastoma cell lines, U87MG and U251MG [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown, among others, that polyphenolic compounds apart from the mentioned mutual combinations could also be combined with other natural compounds such as sugar derivatives, glycosides, peptides, and amino acids [ 51 ]. These studies seemed to be highly relevant in the context of our recent report showing that plant-derived amino acid canavanine (an arginine analog) had a strong cytotoxic effect on two human glioblastoma cell lines, U87MG and U251MG [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 18, 2022. ; https://doi.org/10.1101/2022.02. 18.481112 doi: bioRxiv preprint 4 the incorporation of canavanine into proteins can be detected at a media concentration of about 10 µg/ml [7]. We have shown that respiration-deficient yeasts (petites) produce less arginine than the respiratory WT and that canavanine induces mistargeting of arginine biosynthesis enzymes.…”
Section: Introductionmentioning
confidence: 93%
“…In this way, canavanine has antimicrobial properties and offers protection for the seeds containing it [4]. For years canavanine has been considered as a possible anticancer agent [5, 6], and recently has been shown to have potential as an anti-glioblastoma metabolic therapy when combined with arginine deprivation [7]. In fact, arginine deprivation alone has been shown to induce endoplasmic reticulum stress in solid human cancer cells [8] and arginine deprivation therapy (ADT) is currently being explored as a new metabolic targeting approach with high therapeutic potential for various solid cancers [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 14 articles, different important issues related to glioblastomas are studied, such as resistance to treatment [7][8][9][10], cancer stem cells [7,8,11], metabolism [8,12], epithelial-to-mesenchymal transition (EMT) [11,13] and ROS [9,12,14].…”
mentioning
confidence: 99%
“…Karatsai et al [12] treated arginine-deprived glioblastoma cells with the arginine analogue canavanine, and detected increased apoptotic cell death only in tumor cells, opening the door to metabolic therapy against glioblastoma.…”
mentioning
confidence: 99%